ISMPO Guidelines for Diagnosis and Management of Early Breast Cancer - Singh, Randeep; Sarin, Aditya; Kulkarni, Padmaj; Verma, Amit; Rathi, Arun; Smruti, B. Koppikar; Gupta, Deepika; Govind Babu, Kanakasetty; Malhotra, Hemant; Bajpai, Jyoti; Chandra, Madhavi; Parikh, Purvish; Sharma, Shambhavi; Badwal, Sonia; Mittal, Shivani; Sud, Seema; Gupta, Sudeep; Nag, Shona; Radhakrishnan, Venkat; Aggarwal, Shyam (Indian Journal of Medical and Paediatric Oncology, 2024)
The management of breast cancer has become increasingly complex and multidisciplinary in the recent past. Further, there are unique constraints and opportunities for cancer care delivery in India, including socioeconomic, geographic, and other disparities. Therefore, the Indian Society of Medical and Paediatric Oncology convened a panel of experts to create evidence and context-based guidelines for the management of early breast cancer.
Keywords: early breast cancer; guidelines; ISMPO; medical oncology